Positive cascade effects of forest fragmentation on acorn weevils mediated by seed size enlargement - Bonal, Raul; HERNÁNDEZ, MARISA; ORTEGO, JOAQUÍN; Muñoz, Alberto; ESPELTA, JOSEP M. (Insect Conservation and Diversity, 2012)
Abstract. 1. Today, forest fragmentation is one of the major threats to biodiversity worldwide. In this context, fragmented populations of specialised forest organisms face an increasing risk of extinction because of factors such as local food scarcity. Nonetheless, the role of food availability may differ depending on organism size, which is expected to determine the energy requirements and mobility between fragments. 2. A field study was carried out on Curculio elephas, a forest beetle with low dispersal potential, whose larval development takes place in oak Quercus spp. acorns. 3. For a similar seed crop per tree, acorn size was larger in isolated oaks than in trees located in forest patches. Thus, fragmentation increased local food availability for C. elephas. Larger acorns enabled larval size to increase, a key fitness proxy associated with individual survival, adult size, and potential female fecundity. Indeed, the number of both adults and larvae was higher in isolated trees than in forest patches. 4. In the current scenario of increasing forest fragmentation, the survival likelihood of specialist insects may strongly depend on their ability to adapt to altered environmental conditions. To the best of our knowledge, this is the first study to report on how some forest insects may take advantage of fragmentation-mediated changes to survive in isolated trees. 5. From a conservation perspective, management policies should preserve isolated trees as a source of seeds and fauna for the natural regeneration of forest ecosystems after unproductive farmlands have been abandoned.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn size; Curculio; Forest fragmentation; forest insects; Global change; individual fitness; larval size

Pre-dispersal acorn predation in mixed oak forests: interspecific differences are driven by the interplay among seed phenology, seed size and predator size - ESPELTA, JOSEP M.; Bonal, Raul; Sánchez-Humanes, Belén (Journal of Ecology, 2009)
1. Pre-dispersal seed predation (PSP) often occurs in multi-host–predator systems (e.g. several plant species exposed to a common array of granivorous insects). However, whether the interaction among seed phenology, seed size and predator size accounts for interspecific differences in PSP remains elusive. 2. We studied PSP in a mixed-oak forest with two oaks (the larger-seeded Quercus humilis and the smaller-seeded Q. ilex), both depredated by two acorn weevils (the smaller Curculio glandium and the larger C. elephas). We intensively monitored acorn production and infestation phenology and we identified the weevil species depredating acorns by means of DNA taxonomy. 3. The minimum acorn size required for infestation was lower for C. glandium than for C. elephas, in accordance with their different body sizes. This resulted in an earlier infestation phenology in C. glandium and the ability of this species to infest both smaller and larger acorns. Above a minimum acorn size threshold, no selection for larger acorns by weevils was observed. 4. Initial acorn crop size was similar in the two oaks. Nonetheless, the earlier acorn phenology and the production of larger acorns in Q. humilis favoured the earlier infestation by C. glandium and the predation by both small and large weevils. Smaller acorns of Q. ilex almost excluded infestation by the larger C. elephas. 5. Although larger acorns of Q. humilis could better survive infestation (preserve the embryo), higher PSP in this species finally resulted in a lower mature acorn crop size than in Q. ilex. 6. Synthesis. In a multi-host–predator system, smaller-seeded species may benefit from a reduced PSP because they exclude larger granivorous insects, but also by means of a ‘free-rider effect’, if larger-seeded heterospecifics earlier reach a critical size to be depredated. These results also highlight the benefits of a small body size in granivorous insects to depredate seeds earlier and to forage on a wider range of seed sizes. Whether the advantage of ‘being small’ in this antagonistic plant–animal interaction is offset by other processes, or whether it results in a pressure towards seed and insect size reduction, deserves further attention.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Curculio elephas; Curculio glandium; Mediterranean oak forests; multi-host–predator system; Quercus humilis; Quercus ilex; seed ecology; seed satiation; species coexistence